2001
DOI: 10.1002/etc.5620200930
|View full text |Cite
|
Sign up to set email alerts
|

An interlaboratory study on the use of steroid hormones in examining endocrine disruption

Abstract: In recent years, there has been an increased use of the measurement of sex steroid hormone levels in the blood of animals exposed to chemicals as an indicator of reproductive impairment or an alteration in endocrine function. Although levels of hormones are often compared among animals and laboratories, there has been no study to examine the between-laboratory variability in actual steroid measurements. Therefore, we initiated a study with white sucker collected from a site receiving pulp mill effluent, previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Another challenge for comparative work, is that methods for assaying hormones vary between laboratories (e.g., enzymeimmunoassay vs. radioimmunoassay) and coefficients of variation for identical samples assayed at different labs can be as high as 70.4% (McMaster et al, 2001). Combining corticosterone data from across studies (as in Beaulieu, 2016) is likely to result in spurious conclusions in the absence of controls for differences between experimental assays, and the state of study animals (see above).…”
Section: A Commentary Onmentioning
confidence: 99%
“…Another challenge for comparative work, is that methods for assaying hormones vary between laboratories (e.g., enzymeimmunoassay vs. radioimmunoassay) and coefficients of variation for identical samples assayed at different labs can be as high as 70.4% (McMaster et al, 2001). Combining corticosterone data from across studies (as in Beaulieu, 2016) is likely to result in spurious conclusions in the absence of controls for differences between experimental assays, and the state of study animals (see above).…”
Section: A Commentary Onmentioning
confidence: 99%
“…Analytical method Interlaboratory studies of measured steroid concentrations in white sucker [138,139] relevance, reversibility, and the ability to detect the cause of changes. For example, indicators should have low variability, to have the sensitivity required to detect a change.…”
Section: Methodologicalmentioning
confidence: 99%
“…This would be expected to increase variability in the measurement of these parameters from groups of asynchronous spawning fish. An additional confounding problem is high inter-laboratory variability in the measurement of plasma steroids (McMaster et al, 2001), making it difficult to determine subtle effects on steroid levels and, hence, reducing the sensitivity of the endpoint. Despite these limitations, some authors have concluded that single measures of sex-steroid levels are useful in predicting reproductive dysfunction.…”
mentioning
confidence: 99%